2014
DOI: 10.1242/dev.098657
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor coordinates islet innervation via vascular scaffolding

Abstract: Neurovascular alignment is a common anatomical feature of organs, but the mechanisms leading to this arrangement are incompletely understood. Here, we show that vascular endothelial growth factor (VEGF) signaling profoundly affects both vascularization and innervation of the pancreatic islet. In mature islets, nerves are closely associated with capillaries, but the islet vascularization process during embryonic organogenesis significantly precedes islet innervation. Although a simple neuronal meshwork intercon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 78 publications
6
63
0
Order By: Relevance
“…In mouse, islet vascularization begins during islet cell differentiation (e13.5 onwards), and by birth islets are fully vascularized. While the neuronal processes surround the developing endocrine clusters by e15.5, islet innervation, guided by vascular scaffolds, is completed later around the time of weaning [60]. On the other hand, vascularization and innervation of human fetal pancreas is completed long before birth.…”
Section: Section V: Form Follows Function: Does Islet Morphogenesis Imentioning
confidence: 99%
“…In mouse, islet vascularization begins during islet cell differentiation (e13.5 onwards), and by birth islets are fully vascularized. While the neuronal processes surround the developing endocrine clusters by e15.5, islet innervation, guided by vascular scaffolds, is completed later around the time of weaning [60]. On the other hand, vascularization and innervation of human fetal pancreas is completed long before birth.…”
Section: Section V: Form Follows Function: Does Islet Morphogenesis Imentioning
confidence: 99%
“…Remodeling of the endothelial basement membrane and cellular architecture are required for sprouting angiogenesis, a process similar to epithelial branching morphogenesis (Loibl et al, 2014; Stratman et al, 2009). Innervation patterning and neurovascular co-alignment can also be promoted by shared basement membrane, as in the developing pancreatic islets where the vascular basement membrane is required to guide islet innervation (Reinert et al, 2014). Interestingly, recent data show that basement membranes are functionally asymmetric, with the epithelial side of the basement membrane being laminin-enriched, stiffer, and preferentially binding epithelial cells (Halfter et al, 2013).…”
Section: Co-patterning Of Heterotypic Cell Populations Is An Inherentmentioning
confidence: 99%
“…Although islet endocrine cells produce several angiogenic factors, the development and maintenance of pancreatic islet vasculature is primarily controlled by vascular endothelial growth factor-A (VEGF-A) and VEGF receptor 2 (VEGFR2) signaling, where VEGF-A produced by islet endocrine cells interacts with VEGFR2 expressed on intra-islet endothelial cells (Brissova et al 2006). A series of recent studies has demonstrated that the precise control of VEGF-A production in developing and adult β cells 573324J HCXXX10.1369 is essential for normal islet vascularization, which, in return, regulates several important aspects of islet biology, including β cell mass, function, regeneration and islet innervation (Brissova et al 2006;Lammert et al 2003;Reinert et al 2013;Reinert et al 2014). When VEGF-A is inactivated either in the early pancreas or newly formed β cells, the intraislet capillary plexus fails to fully mature, resulting in substantial defects in β cell proliferation, insulin secretion and glucose homeostasis (Brissova et al 2006;Lammert et al 2003;Reinert et al 2013).…”
Section: Introductionmentioning
confidence: 99%